Circulating Serum Myonectin Levels in Obesity and Type 2 Diabetes Mellitus - Li, Zhu; Yang, Yan-Ling; Zhu, Yan-Juan; Li, Chen-Guang; Tang, Yun-Zhao; Ni, Chang-Lin; Chen, Li-Ming; Niu, Wen-Yan (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective Myonectin is one of the myokines and has gained interest as a potential new strategy to combat obesity and its associated disorders, such as type 2 diabetes mellitus (T2DM).The objective of this study was to investigate circulating serum myonectin levels in nondiabetes and T2DM and elucidate possible relationships between serum myonectin levels and metabolic parameters in patients with T2DM.Design A total of 362 Chinese patients with T2DM and 100 age- and sex-matched healthy controls were recruited in this study. Clinical characteristics, blood biochemistry, and circulating myonectin levels were measured by enzyme-linked immunosorbent assay.Results Circulating myonectin levels were significantly decreased in T2DM compared with controls. Obese nondiabetic controls had significantly lower serum myonectin levels compared with lean nondiabetic controls. In diabetic patients, serum myonectin concentrations were significantly negatively correlated with body mass index (BMI), total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), C-reactive protein (CRP), hemoglobin A1c (HbA1c), fasting insulin (Fins), the homeostatic model assessment of insulin resistance (HOMA-IR), visceral fat area, and subcutaneous fat area. After adjusting for covariates, multivariate stepwise regression analysis demonstrated that BMI, LDL-C, TG, HOMA-IR, and visceral fat were the main independent predictors of low serum myonectin concentrations.Conclusions Circulating myonectin levels were decreased in T2DM patients and in obese subjects. Moreover, serum myonectin levels were correlated with metabolic markers of T2DM. These data suggest that myonectin may be a useful marker in predicting the development of obesity and T2DM.
Keywords: Type 2 diabetes mellitus; serum myonectin; myokine